2001
DOI: 10.1002/jms.184
|View full text |Cite
|
Sign up to set email alerts
|

Metastable ion study of organosilicon compounds. Part XIII: dimethoxydimethylsilane, (CH3)2Si(OCH3)2, and dimethoxymethylsilane, CH3SiH(OCH3)2

Abstract: Unimolecular metastable fragmentations of dimethoxydimethylsilane, (CH(3))(2)Si(OCH(3))(2) (MW 120, 1), and dimethoxymethylsilane, CH(3)SiH(OCH(3))(2) (MW 106, 2), upon electron impact ionization have been studied by means of mass-analyzed ion kinetic energy (MIKE) spectrometry and the D-labeling technique in conjunction with thermochemistry. The results have been compared with those of the corresponding carbon analogues, 2,2-dimethoxypropane, (CH(3))(2)C(OCH(3))(2) (MW 104, 3) and 1,1-dimethoxyethane, CH(3)CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The release of the silicon-based species, such as CH 3 SiH (m/z = 44), between 300 and 700 • C due to the redistribution reactions between the Si-O bonds and Si-H or Si-C bonds was also in good agreement with the literature [35][36][37].…”
Section: Conversion Process: From the Polymer Precursor To Ceramicsupporting
confidence: 88%
“…The release of the silicon-based species, such as CH 3 SiH (m/z = 44), between 300 and 700 • C due to the redistribution reactions between the Si-O bonds and Si-H or Si-C bonds was also in good agreement with the literature [35][36][37].…”
Section: Conversion Process: From the Polymer Precursor To Ceramicsupporting
confidence: 88%
“…The formation mechanisms of the ions at m/z 59 and 45 are well known and therefore they are not presented in this paper. 12 In the case of 3 and 3-d 9 , no molecular ion can be detected in their spectra. However, low-abundant [M CH 3 ] C ions formed by the loss of a methyl radical from the silicon atom are observed as in the case of 1 and 2.…”
mentioning
confidence: 95%
“…No details of the ground state geometry were given, except that a C 2V structure was considered as the ground state conformer. Tajima et al 35 have studied DMDMS by mass-analyzed ion kinetic energy (MIKE) spectrometry. They concluded that the fragmentation pattern for silicon compounds is similar to that of the carbon analogues, thought the mechanism of fragmentation is likely different in the two systems.…”
Section: Introductionmentioning
confidence: 99%